Evaluation of delirium in aged patients assisted at emergency hospital service - Isabella Cristina Barduchi Ohl; Suzel Regina Ribeiro Chavaglia; Rosali Isabel Barduchi Ohl; Maria Carolina Barbosa Teixeira Lopes; Cássia Regina Vancini Campanharo; Meiry Fernanda Pinto Okuno; Ruth Ester Assayag Batista
ABSTRACT Objective: identify the occurrence of delirium in aged patients assisted in emergency services and verify its relationship with sociodemographic and clinical variables. Method: cross-sectional, prospective study with a quantitative approach. Two hundred aged hospitalized patients participated. The Confusion Assessment Method was used for data collection. For statistical analysis, chi-square tests, likelihood ratio and Fisher's test were used, with a significance level of 5%. Results: male gender and mean age of 71.8 years were predominant. In the first 24 hours of hospitalization, 56 (28%) aged individuals presented delirium. An association of the disease with lack of physical activity, presence of a caregiver, hypertension, dyslipidemia and cerebrovascular diseases was identified. Conclusion: Delirium was associated with no physical activity, the need of a caregiver, and the presence of comorbidities. The importance of conducting other studies that may lead to early identification of the condition to prevent its complications is emphasized.